Time–temperature equivalence in the tack and dynamic stiffness of polymer prepreg and its application to automated composites manufacturing - Crossley, Richard J.; Schubel, Peter J.; De Focatiis, Davide S.A. (Elsevier, 2013)
A recently developed peel test designed to simulate the automated tape lay-up (ATL) process was used to measure tack and dynamic stiffness of newly developed ATL prepregs. Resin was extracted from the prepreg process before impregnation of the fibres. Isothermal small amplitude frequency sweeps were carried out in shear rheology to determine time–temperature superposition parameters in the form of Williams–Landel–Ferry equation. Gel permeation chromatography and differential scanning calorimetry demonstrated that the resin was not significantly changed during the prepregging process. The WLF parameters were used to transpose isothermal tack and dynamic stiffness results with excellent agreement found. This relationship offers manufacturers using composite prepreg a method to maximise and maintain tack levels at different feed rates by appropriate changes in temperature. This is of significant importance in improving the reliability of automated composite lay-up processes such as AFP and ATL, whose feed rate must vary to accommodate lay-up operations.